Large-eddy simulation of the injection timing effects on the dual-fuel spray flame. (15th February 2022) - Xu, Shijie; Zhong, Shenghui; Hadadpour, Ahmad; Zhang, Yan; Pang, Kar Mun; Jangi, Mehdi; Fatehi, Hesameddin; Bai, Xue-Song
Abstract: Large-eddy simulations (LES) coupled with a partially-stirred reactor model and a finite-rate chemistry are carried out to investigate the effects of n-heptane injection timing on the methanol fueled dual-fuel (DF) combustion. Methanol is premixed with air in a constant volume chamber ( T =1000 K, ρ =14.8 kg/m 3 ) to form a homogeneous mixture (equivalence ratio ϕ m of 0.3). Liquid fuel n-heptane is provided from a high pressure injector to mimic the pilot fuel injection in DF engines. First, mesh sensitivity analysis and LES model validation are conducted. The experimental data of Spray-H (n-heptane fueled) from the Engine Combustion Network is used for model validation. It is shown that the present mesh and LES model are capable of replicating the liquid and vapor penetration length, mixture fraction, temperature distribution, pressure rise profile and ignition delay time (IDT). Second, the effects of n-heptane injection timing are investigated, by varying the start of injection (SOI) time. The LES results reveal that there are three stage heat releases in the DF combustion. With the delay of SOI, the mass fraction of hydrogen peroxide in the ambient mixture increases, leading to an early formation of hydroxyl. Therefore, the two-stage IDTs of n-heptane decrease, while the ambient methanol IDT increases. Results also show the cool flame and high-temperature flame evolution after methanol auto-ignition. The cool flame disappears while the high-temperature flame is found near the injector nozzle, which leads to a relatively high heat release rate. Highlights: LES of methanol/n-heptane dual-fuel spray ignition/flame interaction is studied. Three-stage heat release is found under high temperature and pressure conditions. A delayed injection leads to a shorter IDT of n-heptane and longer IDT of methanol. The injection timing affects the cool flame and high temperature flame structure.